Gender influence on white matter microstructure: a tract-based spatial statistics analysis. - Richard A Kanaan; Christopher Chaddock; Matthew Allin; Marco M Picchioni; Eileen Daly; Sukhi S Shergill; Philip K McGuire (PLoS ONE)
Background Sexual dimorphism in human brain structure is well recognised, but less is known about gender differences in white matter microstructure. We used diffusion tensor imaging to explore gender differences in fractional anisotropy (FA), an index of microstructural integrity. We previously found increased FA in the corpus callosum in women, and increased FA in the cerebellum and left superior longitudinal fasciculus (SLF) in men, using a whole-brain voxel-based analysis. Methods A whole-brain tract-based spatial statistics analysis of 120 matched subjects from the previous analysis, and 134 new subjects (147 men and 107 women in total) using a 1.5T scanner, with division into tract-based regions of interest. Results Men had higher FA in the superior cerebellar peduncles and women had higher FA in corpus callosum in both the first and second samples. The higher SLF FA in men was not found in either sample. Discussion We confirmed our previous, controversial finding of increased FA in the corpus callosum in women, and increased cerebellar FA in men. The corpus callosum FA difference offers some explanation for the otherwise puzzling advantage in inter-callosal transfer time shown in women; the cerebellar FA difference may be associated with the developmental motor advantage shown in men.